Analisis Manajemen Stok Pergudangan di Perusahaan Distribusi Cirebon - Yudistira, Fairuuz; Bagaskara, Allan I.; Musyaffa, Muhammad A.; Fitriani, Putri A. (Training & Research Institute - Jeramba Ilmu Sukses, 2024)
The warehouse management system manages every activity in the warehouse, from the receiving process to delivery. One of the problems that occurred in the PT. Warehouse. Fastrata Distribution Indonesia, namely processing data on incoming and outgoing goods, is still manual. This problem can result in a mismatch between the data and the goods in the warehouse. This research aims to find out information about the stock management system at PT. Fastrata Indonesian Distribution. Qualitative descriptive research is the method used. The research results show that PT. Fastrata Distribution Indonesia uses the FEFO (First Expired, First Out) system. However, the goods dispensing system still uses manual checks by user checkers. This manual check issuance system is still not practical, so it is recommended that companies use a Warehouse Management System (WMS).